A promising independent prognostic biomarker in colorectal cancer: P2X7 receptor - Calik, Ilknur; Calik, Muhammet; Turken, Gulistan; Ozercan, Ibrahim Hanifi (E-Century Publishing Corp, 2020)
The P2X7 receptor (P2X7R) is an exclusive member of the purinergic receptor family that plays a key role in tumor progression, including colorectal cancer (CRC). P2X7R supports the tumor cells to resist unfavorable conditions by stimulating GLUT-1 expression. GLUT1 is the major glucose transporter in CRC cells and is indicated to be a poor prognostic indicator in patients with CRC. Recently, P2X7R and GLUT-1 are being investigated as prognostic biomarkers in the development of new treatment options. In this study, we aimed to investigate the prognostic value of P2X7R and GLUT-1 expression in CRC. We examined P2X7R and GLUT-1 expression in specimens of 196 CRC patients, immunohistochemically. P2X7R expression was higher in patients with poorly differentiated tumors than in those with well differentiated ones (P = 0.001). P2X7R and GLUT-1 overexpression were correlated to TILs (P<0.001; P = 0.028, respectively), depth of invasion (P<0.001; P = 014, repectively), distant metastasis (P<0.001), and advanced TNM stage (P<0.001). Moreover, multivariate Cox regression analysis showed that P2X7R overexpression clearly correlated with worsened overall survival (HR 4.69; 95% CI 1.77-12.41; P = 0.002). Similarly, patients with GLUT-1 overexpression showed shorter overall and disease-free survival than those with low expression. Our data support that P2X7R and GLUT-1 may be used as an independent prognostic markers and may present new options in terms of targeted therapies for CRC patients.
Keywords: P2X7R; colorectal cancer; GLUT-1; TILs; prognosis